Evidence-based management of dermatophytosis in India today - Aparajita Ghosh; Saumya Panda (Apollo Medicine)
Introduction: Dermatophyte infection has become extremely resistant and widespread in all parts of India during the past decade. A change in the major causative organism has been identified to be a major factor behind the change in the character of the infection. The epidemiological shift has been accompanied by large scale antifungal resistance. This review aims to take a look at the current status of evidence regarding the effectiveness of major antifungal molecules, with particular reference to the current epidemic-like scenario of resistant dermatophytosis in India. Methods: We have searched and included the relevant literature on “Dermatophytosis” from the PubMed, Scopus, and Google Scholar. Results: The current situation has also brought into focus the glaring lack of evidence-based guidelines for the management of dermatophytosis. The guidelines available previously had mostly been based on the western literature with the scarcity of studies from tropical countries such as India. Conclusion: The current guidelines of the management of dermatophytosis have lost their relevance in the present scenario and need to be replaced. However, without adequate studies we do not have robust data to formulate the new guidelines.